Pengaruh Kualitas Audit dan Auditor Baru serta Pengalaman Bagian Akuntansi terhadap Kepuasan dan Loyalitas Klien - Sugeng Pamudji (Jurnal Akuntansi dan Auditing Indonesia, 2009)
The objectives of this study are to prove and analyze four hypothesis proposed; the influence of audit quality on client satisfaction, the influence of controller experience on client satisfaction, the influence of new auditor on client satisfaction, and the influence of client satisfaction on client loyalty.360 companies listed in Jakarta Stock Exchange in 2005 were asked to participate in the study but only 65 questionnaires were collected. The primary targets for data collection were: controller, internal auditor, and audit committee. Purposive sampling Technical is used in data collection and the data was analyzed using SEM (Structural Equation Modelling) supported with AMOS Software.The results explained the relationship between audit quality, new auditor, controller experience, client satisfaction, and client loyalty.  Based on the data analysis, two hypotheses are accepted and two hypotheses are rejected. Audit quality has significant influence on client satisfaction. Client satisfaction has significant influence on client loyalty. However, new auditor (auditor change) and experience of controller has no significant influence on client satisfaction. There are several limitations of the study: minimum sample in maximum likelihood estimation (100) and the dimensions of New Auditor variable and controller experience that need to be extended.Keywords:    audit quality, new auditor, controller’s experience, client satisfaction, and client loyalty